Analisis Retorika Visual Iklan Gojek di Kanal YouTube Untuk Mengajak Masyarakat Menggunakan Beragam fitur Yang Tersedia di Aplikasi Gojek Indonesia - Kezia, Yohana; Rizky, Alya; Hendratno, Adityawan; Taufiqulhaq, Moh Fikri; Kirana, Citra Dewi; Sholihatin, Endang (Jurnal Ilmiah Wahana Pendidikan, 2025)
The world of marketing and advertising is now increasingly developing with the internet and social networks which play a big role in various areas of life through marketing and advertising. In Indonesia in particular, marketing through advertising on social media is very diverse and each company has its own characteristics in offering their products and services, one of which is Gojek. This research aims to determine the rhetoric and visualization of advertising in the feature offerings made by the Gojek company to attract/stimulate the interest of the Indonesian people in using the Gojek application. The method used in this description is a qualitative method. The conclusion of this research is that the advertising rhetoric and visualization in offering features by the Gojek company to attract/stimulate the interest of the Indonesian people to use it, namely: a) the use of persuasive word selection strategies to encourage consumers to use the Gojek application because of the service features provided can be used remotely, easily and quickly so that consumers do not need to be confused when they need something in any circumstances and is more practical; b) Gojek company's creative marketing strategy, such as choosing a video concept, offering relatively cheap and affordable prices, and providing lots of discounts.